Potential Antitubercular Agents, Part I: 4-Thiazolidinone Derivatives - Solankee, Anjani; Kapadia, Kishor; Turel, J.M. (Asian Journal of Chemistry, 2010)
4-Thiazolidinones have been prepared by condensing α-bromoadipic acid with different thioureas. The 4-thioazolidinones have been tested for antitubercular activity using H37RV strain of bacteria.